USA Gymnastics selects two clubs for first phase of trampoline development programm (Technique, 2013)
USA Gymnastics has selected two clubs to participate in the first phase of its pilot program to develop trampoline and tumbling in the United States. Mills Gymnastics USA in Soulhgale, Mich., and the Wendy Hilliard Foundation in New York City have been chosen as the first clubs to become Trampoline Development Centers. The initiative's goal is to incorporate competitive trampoline into the curriculum in gyms across the nation to expand its Olympic pipeline.